Role of presynaptic glutamate receptors in Modulation of long term synaptic plasticity (LTP) in inhibitory synapes of visual pyramidal neuron after epilepsy: a whole cell patch clamp recording - Reza, Mohammed Faruque (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2015)
Purpose: Results from animal models has pointed out that presynaptic NMDA (pre-NMDA) receptor is present in visual cortex and pre-NMDA has significant role in epilepsy. Therefore we have tested the role of pre-NMDA receptor for GABA-ergic transmission in the visual cortex in acute condition of epilepsy. Methods: Using the pilocarpine mouse model, visual cortical slices were prepared immediately after having seizure (Pilo.group), and spontaneous miniature IPSCs (miPSCs) were recorded from pyramidal neurons of layer II/III in visual cortex. Amplitudes and frequencies of miPSC were analyzed and compared with those in age-matched saline-injected controls. Results: Frequency of miniature IPSCs (miPSCs) were significantly increased in saline controls compared to Pilo. Amplitude has no significant difference among groups using NBQX only or NBQX and MK801 combined use. Conclusion: In acute condition of epilepsy, there is no significant role of presynaptic NMDA receptor for GABA-ergic neurotransmitter release which is a indicator of long term potentiation (L TP) of inhibitory synapses.